ICT, the Somali diaspora and the stabilization of a failed state - Elmi, Mohamed Abokor (Department of Information Systems, 2020)
For almost three decades, Somalia has defied definition and expectation precisely because the country has lacked an effective, centralized state apparatus. As a result, the term 'failed state’ is often applied to Somalia in popular discourse and by scholars. For a state to formally function as such, a few conditions must be met including the state’s ability to unquestionably legitimatize its authority over its territory, its residents pledging allegiance to that state, and explicit recognition by other states. Despite the perceived chaos and violence associated with the country, there is evidence of structures that allow for markets to function and social services to be delivered. The Somali diaspora is one factor in supporting Somalia’s economic and social system, as remittances pay for children’s education, social services and provide investment funds for businesses. Moreover, Somalia has been able to foster a vibrant Information Communications Technologies (ICTs) sector, comparable to that of its more stable and wealthier East African neighbours. Therefore, the objective of this Information Systems thesis is to examine how Information Communication Technologies are utilized within communities that are considered failed (or failing) and lack defined, and legitimate state apparatus. The guiding research question for this thesis is: What role does Information and Communication Technologies (ICTs) and the diaspora play in the creation of a `stable` Somalia? To address the research question, in addition to providing Somalia’s historical context, three interrelated empirical studies were designed. The first study utilizes both qualitative and quantitative content analysis approaches to extend our understanding of how Somalia is defined in Western media. This included determining when the failed state term became synonymous with Somalia. The study, additionally, applies the principles of Critical Discourse Analysis to explore how Somalia and Somalis are perceived and portrayed in Western news sources. The study confirmed that Western media narratives about the country are negative in tone, violent in the description and have reinforced negative stereotypes regarding Somalia and its people. The second study explores the existing social structures in Somalia, utilizing Anthony Giddens’s Structuration Theory. More specifically, the study examines the banking and credit system used by Somalis, how the education and justice systems are delivered along with other necessary social services accessed by residents within the country. Through in-country key Mohamed Elmi PhD. Thesis iv informant interviews from various sectors and industries, the study aimed to discover how visible and invisible institutions that are central to the delivery of social and economic services in Somalia are mediated by ICTs. This study found evidence of functioning social structures, despite the failed state label applied to Somalia. The third study aimed, through surveys and key informant interviews, to better understand the role played by the diaspora in Somalia’s economic and social system. This study explores the institution behind the Hawala system and how it is enabled by technology. By examining how the remittance system works and the methods Somalis employ including recent innovations such as mobile banking, this study also establishes the role of Information Communication Technologies (ICTs) in the Somali money transfer sector. In the concluding chapter, the contributions to both the Information Systems field and our collective understanding of Somalia are discussed. Drawing on the evidence from the three studies, this chapter makes four main claims. The first claim of this study is that ICTs act as a binding agent of social structures within Somalia as defined by a social theory framework. I am thus demonstrating why Somali social institutions function in the absence of a robust administrative state. The second claim argues that the diaspora are essential agents in stabilizing Somali social and economic institutions by offering financial aid, investments and knowledge transfer. The third claim suggests that the perceptions of Somalia and its people have been negatively influenced by Western news media. Finally, I argue that definitions of a failed state are narrow, Western-centric and do not necessarily apply to Somalia.